Physicians’ attitude and perception regarding celiac disease: A questionnaire-based study - Jinga, Mariana; Popp, Alina; Balaban, Daniel Vasile; Dima, Alina; Jurcut, Ciprian (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Despite its high prevalence, affecting about 1% of the general population, celiac disease (CD) remains heavily underdiagnosed. Among the reasons for underdiagnosis, awareness among medical professionals has been little studied. The aim of this survey was to determine physicians’ knowledge in regard to CD in adult patients. Materials and Methods: An 18-items questionnaire pointing out general features, clinical presentation, diagnosis and management of CD patients was addressed to physicians from different medical specialties, in training or board-certified, from one universitary center. Results: Altogether 153 physicians were invited to complete the survey (69.3% female, 35.9% gastroenterologists). Overall, 69.9% of the physicians questioned considered CD as a rare disorder. Lymphoma increased risk was highlighted in significant higher proportion by gastroenterologists when compared with physicians of other medical specialty. Chronic diarrhea, weight loss, iron-deficiency anemia, and abdominal pain were the first four conditions recognized as associated with CD, by 94.1%, 76.5%, 61.4%, and 54.2% study participants, respectively. About one-third of respondents (34.5%) affirmed to perform total serum IgA testing in all patients tested for CD. Intestinal biopsy confirmation of a positive celiac serology was reported by 65.4% physicians, with a higher proportion among gastroenterologists: 81.5% versus 56.6%. In regard to CD management, both groups concluded that referral to specialized centers should be recommended. Conclusion: This study highlights poor awareness among the physicians’ in regard to important CD features and diagnostic recommendations in adult patients. More efforts are warranted to improve awareness on CD features among physicians of different medical specialties. Cite this article as: Jinga M, Popp A, Balaban DV, Dima A, Jurcut C. Physicians’ attitude and perception regarding celiac disease: A questionnaire-based study. Turk J Gastroenterol 2018; 29: 419-26.